Territorial cohesion cities: a policy recipe for achieving territorial cohesion? - Medeiros, E.; Rauhut, D. (Regional Studies, 2020)
This paper discusses the role of medium towns as crucial anchors in achieving the policy goal of Territorial Cohesion. It highlights the need to counterbalance market trends to favour the continuous channelling of investment and people into larger metropolitan areas by way of proactive measures focused on attracting investment into medium towns, and as an alternative to dispersing public and private investment in lagging territories. Iberian and Nordic cases are examined in order to illustrate the possibilities and challenges of using ‘Territorial Cohesion Cities’ as development hubs in lagging regions, in order to achieve Territorial Cohesion at a national level.